Nilai-Nilai Pendidikan Agama Islam - Tamrin Tamrin (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2020)
The problem that has been forgotten, abandoned and never received more is the problem of value. One thing that becomes more fundamental is how humans become more mature and able to live a more respectful life based on values ​​and conscience so as to bring out the whole human character (insan kamil). An interesting question often arises, can values ​​be taught? Questions like this can arise among educators, academics, or the wider community. So many people then discussed this issue. This shows a great deal of attention to this issue, and the answer to that question is very clear that values ​​can be taught through the educational process. To realize the value of good and quality education, it is necessary to have supporting components, one of which is the professional performance of teachers. Teacher performance is the key to the success of education, because the presence of teachers is very influential on all existing educational resources such as facilities and infrastructure, costs, technology, information, students and parents of students can function properly if the teacher has a good ability to use all existing resources.